Perception of Polish Democracy in a Comparative Approach in Relation to the European Integration Processes - Grosse, Tomasz Grzegorz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The aim of the article is to show the condition of Polish democracy on the example of two elections held in 2019 and 2020. The elections brought about a positive phenomenon for democ racy, which is an increase in voter turnout. On the other hand, negative phenomena appeared, in particular the violent political polarization within the political community. The example of the Polish elections was then confronted with the perception of democracy among Polish society in a comparative approach, i.e. against the perception of other European nations. Against this background, the assessment of Polish democracy by Poles is exceptionally positive. Later in the article, an attempt was made to consider to what extent the integration processes may be responsible for weakening democracy in the Member States, as well as for the decline in trust in democratic institutions in the west and southern part of the continent.

Celem artykułu jest ukazanie kondycji polskiej demokracji na przykładzie dwóch wyborów przeprowadzonych w 2019 i 2020 roku. Wybory przyniosły pozytywne zjawisko z punktu widzenia jakości demokracji, jakim jest wzrost frekwencji wyborczej. Z drugiej strony pojawiły się negatywne zjawiska, w szczególności gwałtowna polaryzacja polityczna w ramach wspólnoty politycznej. Przykład wyborów w Polsce i postrzeganie demokracji w społeczeństwie polskim zostały pokazane w ujęciu porównawczym, czyli w odniesieniu do percepcji demokracji u innych narodów europejskich. Na tym tle ocena krajowej demokracji przez Polaków jest wyjątkowo pozytywna. W dalszej części artykułu podjęto próbę rozważenia, w jakim stopniu procesy integracyjne mogą odpowiadać za osłabienie postrzegania demokracji w państwach członkowskich, a zwłaszcza za spadek zaufania do instytucji demokratycznych w zachodniej i południowej części kontynentu.
Postrzeganie polskiej demokracji w ujęciu porównawczym w odniesieniu do procesów integracji europejskiej
Keywords: democracy; political polarization; European integration; Poland; demokracja; polaryzacja polityczna; integracja europejska; Polska